Analisis pengendalian kualitas gula kristal putih melalui penerapan metode Statistical Quality Control (SQC) pada PT. XYZ - Aulia, Xenia Amanda; Winursito, Yekti Condro (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Improving product quality is one of the important factors in facing industrial competition, especially in the White Crystal Sugar (GKP) production sector. PT XYZ, as one of the GKP producers, faces challenges in maintaining the consistency of its product quality according to applicable standards. This study aims to assess the quality of the production process at PT.XYZ by utilizing the Statistical Quality Control (SQC) method through the use of a p-control map (P-Chart) to measure the proportion of defective products. The analysis was conducted on 29 production samples. The results show that the production process is in statistical control, with an average defect proportion of 0.006984, where all points are between the upper control limit (UCL = 0.008769) and the lower control limit (LCL = 0.005199). The defect rate found is very small, less than 0.1%. The total defects reached 3279 kg GKP, consisting of color defects of 1155 kg (35.22%), moisture content of 1091 kg (33%), and cleanliness of 1033 kg (32%). Based on the fishbone diagram, the defects were caused by workers, machines, operational methods, and production materials. In conclusion, the application of the SQC method is effective in identifying and controlling factors that affect the quality of GKP at PT XYZ.